The prevalence of Passavant's ridge in patients with velopharyngeal insufficiency in a Taiwan Chinese population - Hung-Chun Lin; Chung-Hsiao Cheng; Gin Chen (Elsevier, 2019)
Background/purpose: The Passavant's ridge can be utilized as a guide landmark during obturator prosthesis fabrication, but there were no studies concerning about the prevalence of the ridge in East Asia region. The purpose of this study was to evaluate the occurrence of Passavant's ridge in patients with velopharyngeal insufficiency in a Taiwan Chinese population. Materials and methods: It's a retrospective study that 91 patients with velopharyngeal insufficiency who received a obturator prosthesis during the period from 1992 to 2016 in Taichung Veterans General Hospital (TCVGH, Taiwan) were included. The Passavant's ridge was directly identified under intraoral examination during phonation (group 1) and gagging (group 2) action by two examiners. The results in these two groups were compared using McNemar test. Associations between the presence of the ridge and categorical variables (gender, etiology and defect area) were also analyzed using the chi-square test or Fisher's exact test. (α = 0.05) Results: Passavant's ridge was observed during phonation in 72 patients (79.1%) and during gagging in 83 patients (91.2%), which showed a statistically difference (p < 0.05). The relationship between the presence of the ridge and categorical variables (gender, etiology and defect area) were evaluated but no statistically significant correlation was found (p > 0.05). Conclusion: A high prevalence of Passavan't ridge either in phonation and gagging action was identified in patients with velopharyngeal insufficiency in a Taiwan Chinese population. In addition, the occurrence of Passavant's ridge was significantly higher during gagging action than during phonation. Keywords: Prosthetics, Soft palate, Velopharyngeal function